Analysis of Comparative Fiqh: Conventional Bank Versus Islamic Bank - Lutfiyah, Lutfiyah; Nazih, Nazih Sadatul Kahfi; Fatmawati, Nilal Muna; Hakim, Muhammad Abdul Rahman; Fanani, Muhyar (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
What happens in the community about the concept of bank interest and profit sharing there are different perspectives. Bank interest is often regarded as usury in Islam, as it is contrary to Sharia principles. In contrast, the profit-sharing system in Islamic banks is seen as fairer because it is in accordance with Islamic teachings. Understanding the difference between conventional bank interest and the mudharabah system in fiqh law is very important in the context of justice in Islam. So, the focus of this research is the analysis of the interest system in conventional banks and profit sharing in Islamic banks in the perspective of fiqh law. The method used is library research, as it has reviewed from several reading materials articles and books. The results of this study indicate that the majority of scholars consider bank interest as usury, which is prohibited in Islam, because it causes injustice and economic exploitation. Meanwhile, mudharabah is considered in accordance with Sharia principles because it fulfills the concepts of justice, transparency, and partnership in sharing risks and profits.